Impact of Sampoerna Retail Community (SRC) CSR Program on Grocery Stores - Wardati, Ela; Kambali, Muhammad (Journal of Social Science and Economics, 2023)
The presence of modern retail, minimarkets, and supermarkets makes the existence of traditional stores that have long been rooted and become part of the culture of the Indonesian nation, grocery stores began to be affected by its progress. Creativity and innovation are needed in maintaining the progress of the grocery store. The presence of Sampoerna Retail Community CSR program is the answer to the needs of grocery store entrepreneurs in competition with modern retail. This study aims to answer the problem of whether there is a significant impact of Sampoerna Retail Community's CSR program on the progress of grocery stores. This type of research is Field Research field research with a quantitative approach. Data was collected using a closed questionnaire technique with Likert scale. A population of 35 SCR partners with population sample sampling techniques or saturated samples. The data were analyzed using simple linear regression statistical tests, T test and R2 test. The results of this study conclude that there is a significant influence of Sampoerna Retail Community (SRC) CSR program on the progress of grocery stores. The amount of impact produced is 7.3% as the results of the R2 test. The results of this study strengthen previous research that CSR programs are very helpful or have a positive impact on people's lives. Similarly, PT HM Sampoerna Tbk's Sampoerna Retail Community (SRC) CSR program is the answer to the problems of grocery store entrepreneurs in their competition with modern retail